Analysis of Farmer’s Intention to Adopt The I-Pubers Application for Redemption of Subsidized Fertilizer in Madiun Regency - Aris Setyowiyono; Amalia Arsha Adeniar; Reza Auliarizky Arbianputra; Hardiyansyah Hardiyansyah (Revenue Journal: Management and Entrepreneurship, 2026)
Subsidized fertilizer is crucial for food self-sufficiency, but faces challenges in transparency, distribution accuracy, and digitalization. This study analyzed farmer’s intentions in Madiun Regency to use the i-Pubers application using the Technology Acceptance Model (TAM) approach. The quantitative-associative method was used, with primary data collected from 197 respondents using a Likert scale questionnaire, analyzed using SEM-PLS. The results had shown that government support and social learning did not affect perceived ease of use, but significantly affect perceived usefulness, while platform support influences both. Perceived ease of use and perceived usefulness influence attitudes toward use, which in turn impacts adoption intentions. This study contributes to improving the transparency and efficiency of fertilizer distribution and supports SDGs 9 through agricultural digitalization.